A formação da(s) identidade(s) em O último voo do flamingo e Terra sonâmbula - Pinheiro, Beatriz Costa Lima (2021)
This work investigates how the Mozambican writer Mia Couto chooses to represent the identities of his characters in two novels: Terra sonâmbula (2007) and O último voo do flamingo (2005). The two novels fictionalize two episodes that are very representative in the history and for the Mozambican population; Terra sonâmbula takes place during the civil war that ravaged the country from 1976 to 1992 and O ultimo voo do flamingo illustrates the post-war period, the consequences and corruption of the current government, in addition to portraying traditional elements of African rural cultures and their symbolism during the narratives. The research was conducted using as a corpus the novels already cited and based on Stuart Hall's reflections on identity in postmodern society, with a focus on post-colonial societies, the studies of Frantz Fanon, published in his book Peles negras, mascaras brancasa (2008) on colonial society from a black perspective and experience, an author who was largely responsible for the freedom movements across the world, even though his texts were not thought for the post-colonial moment. This dissertation also counts on the contributions of theorists Edouard Glissant, Homi Bhabha and Zilá Bernd with regard to the processes of assimilation, hybridization, miscegenation and creolity, which are essential to understand the diverse processes that led to the formation of the unique and distinct identities designed by the author, and Joel Candau, responsible for the theory of fluid memory and its contribution and influence on identities based on the social environment and traditions presented to the individual at various stages of life. In addition to the contribution of these thinkers, the research also draws on criticism specialized in Mia Couto and his work, such as Sueli Saraiva who analyzes the narratives relationship with the historical context and time itself and Evillyn Kjellin in the analysis of the complexity of female characters created by Mia Couto, among other authors whose work is cited here. It was also important to understand the historical political and social processes that occurred in Mozambique in the last 50 years and how these changes impacted both the reality of Mozambicans and their mentality and finally, how these processes were represented by the author and their influence on the identities of the characters analyzed here.